Nanotribology at high temperatures - Goel, Saurav; Stukowski, Alexander; Goel, Gaurav; Luo, Xichun; Reuben, Robert L. (Beilstein Journal of Nanotechnology, 2012)
Recent molecular dynamics simulation results have increased conceptual understanding of the grazing and the ploughing friction at elevated temperatures, particularly near the substrate’s melting point. In this commentary we address a major constraint concerning its experimental verification.
Keywords: CBN; diamond; high temperature